THE LIVERWORT GENUS Marchantia (Marchantiaceae) OF MOUNT SIBAYAK NORTH SUMATRA, INDONESIA - Siregar, Etti Sartina; Ariyanti, Nunik S.; Tjitrosoedirdjo, Sri S. (BIOTROPIA, 2013)
Study on the Hepaticae (Liverworts) of Sumatra is very scanty including the knowledge on the genus of Marchantia (Marchantiaceae). This study was conducted to explore the diversity of Marchantia in Mount Sibayak North Sumatra, Indonesia. There are seven species of Marchantia in Mount Sibayak North Sumatra, five of the species are previously known: Marchantia acaulis, M. emarginata, M. geminata, M. paleacea, and M. treubii; two of the species are new records for Sumatra (M. polymorpha and M. rubribarba). An identification key of the genus Marchantia from Mount Sibayak, North Sumatra is provided.